Developing the TeamOBS-vacuum-assisted delivery checklist to assess clinical performance in a vacuum-assisted delivery: a Delphi study with initial validation - Brogaard, Lise; Hinshaw, Kim; Kierkegaard, Ole; Manser, Tanja; Uldbjerg, Niels; Hvidman, Lone (Frontiers in Medicine, 2024)
Introduction In Northern Europe, vacuum-assisted delivery (VAD) accounts for 6–15% of all deliveries; VAD is considered safe when conducted by adequately trained personnel. However, failed vacuum extraction can be harmful to both the mother and child. Therefore, the clinical performance in VAD must be assessed to guide learning, determine a performance benchmark, and evaluate the quality to achieve an overall high performance. We were unable to identify a pre-existing tool for evaluating the clinical performance in real-life vacuum-assisted births. Objective We aimed to develop and validate a checklist for assessing the clinical performance in VAD. Methods We conducted a Delphi process, described as an interactive process where experts answer questions until answers converge toward a “joint opinion” (consensus). We invited international experts as Delphi panelists and reached a consensus after four Delphi rounds, described as follows: (1) the panelists were asked to add, remove, or suggest corrections to the preliminary list of items essential for evaluating clinical performance in VAD; (2) the panelists applied weights of clinical importance on a Likert scale of 1–5 for each item; (3) each panelist revised their original scores after reviewing a summary of the other panelists’ scores and arguments; and (4) the TeamOBS-VAD was tested using videos of real-life VADs, and the Delphi panel made final adjustments and approved the checklist. Results Twelve Delphi panelists from the UK (n = 3), Norway (n = 2), Sweden (n = 3), Denmark (n = 3), and Iceland (n = 1) were included. After four Delphi rounds, the Delphi panel reached a consensus on the checklist items and scores. The TeamOBS-VAD checklist was tested using 60 videos of real-life vacuum extractions. The inter-rater agreement had an intraclass correlation coefficient (ICC) of 0.73; 95% confidence interval (95% CI) of [0.58, 0.83], and that for the average of two raters was ICC 0.84 95% CI [0.73, 0.91]. The TeamOBS-VAD score was not associated with difficulties in delivery, such as the number of contractions during vacuum extraction delivery, cephalic level, rotation, and position. Failed vacuum extraction occurred in 6% of the video deliveries, but none were associated with the teams with low clinical performance scores. Conclusion The TeamOBS-VAD checklist provides a valid and reliable evaluation of the clinical performance of vaginal-assisted vacuum extraction.